Narracja z perspektywy dziecka w cyklach opowiadań "Nienawiść" i "Strach" Stanisława Srokowskiego = The narration from the perspective of a child in the series of stores "Nienawiść" and "Strach" by Stanisław Srokowski - Bąk, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In Stanisław Srokowski`s short stories "Nienawiść" and "Strach", the massacre in Volhynia is presented to the reader from the viewpoint of a child - a boy, the youngest witness of the events. The boy is a fictional character created by the author to tell us the story of a massacre. The semichild narrative is used in those stories intentionally so as to add the psychological, linguistic and literary dimension. This specific narrating strategy used by Srokowski in his short stories helps the reader to understand the problem of a child factor - a silent victim of a war conflict created by the adults.
Keywords: narration; narrating strategy; perspective of a child; Srokowski, Stanisław (1936- ); narracja; dziecięca perspektywa; strategia narracyjna